The Reason of Indonesia Postponement Towards The Ratification of The Who's Framework Convevtion on Tobacco Control (FCTC). - Amirul Mahar Patitisan (HI 14 UMY 065, 2014)
This research aims to explain the problem of tobacco control in Indonesia and mainly to look for the factor which is influencing Indonesian postponement on the ratification towards the WHO’s Framework Convention on Tobacco Control (FCTC) while the ratification itself seems to be very important. The linked theoretical framework of hyperpluralist theory will be best explaining on why Indonesia keeps on postponing the ratification of the WHO’s FCTC. The research area covers from 2003 when the FCTC was established until 2014 when FCTC has not even been ratified by Indonesia. The finding of this research shows that interest groups which mainly come from the tobacco industry influence the government’s decision especially in health matter related to the policy on tobacco control. Though there are economy, social and political reasons, the main reason of the postponement of FCTC ratification by Indonesia is caused by the strong lobbying of the cigarette industry. The interest groups enter the government’s decision making process through the more legal group such as political parties which have some representatives in the legislative body. The tobacco industries use the welfare of tobacco farmers as a shield to impede the government to ratify the FCTC. The electoral support and via lobby through bureaucracy are very influential in the government’s decision making.